2001
DOI: 10.1016/s0378-1097(01)00100-8
|View full text |Cite
|
Sign up to set email alerts
|

PCR detection of Brachyspira aalborgi and Brachyspira pilosicoli in human faeces

Abstract: Previously-developed PCR protocols specific for the 16S rRNA gene of the intestinal spirochaetes Brachyspira aalborgi and Brachyspira pilosicoli were adapted for the detection of these species in human faeces, following DNA extraction and purification using mini-prep columns. The limits of detection in seeded faeces for B. aalborgi and B. pilosicoli respectively were 2U10 2 and 7U10 3 cells per PCR reaction, equivalent to 5U10 4 and 1U10 5 cells per g of faeces. The PCR techniques were applied to faecal sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 18 publications
2
24
0
1
Order By: Relevance
“…The sensitivity of PCR for detection of B. hyodysenteriae was higher than that for detection of B. pilosicoli and similar to the sensitivity of culture. The sensitivities of PCRs targeting the 23S rRNA genes or other genes of Brachyspira species for various species of intestinal spirochaetes have been reported (Park et al, 1995;Leser et al, 1997;Atyeo et al, 1998;Barcellos et al, 2000;Mikosza et al, 2001). These PCRs were applied directly to spirochaete cells or to spirochaetal growth on primary isolation plates, and their sensitivities were generally consistent with those of the PCR used in the present study.…”
Section: Resultssupporting
confidence: 82%
“…The sensitivity of PCR for detection of B. hyodysenteriae was higher than that for detection of B. pilosicoli and similar to the sensitivity of culture. The sensitivities of PCRs targeting the 23S rRNA genes or other genes of Brachyspira species for various species of intestinal spirochaetes have been reported (Park et al, 1995;Leser et al, 1997;Atyeo et al, 1998;Barcellos et al, 2000;Mikosza et al, 2001). These PCRs were applied directly to spirochaete cells or to spirochaetal growth on primary isolation plates, and their sensitivities were generally consistent with those of the PCR used in the present study.…”
Section: Resultssupporting
confidence: 82%
“…The PCRs used for the detection of B. pilosicoli and B. aalborgi were the same as described previously for identification of the two organisms in human faeces [11,19], with the primers and PCR conditions being as described by Mikosza and colleagues [3].…”
Section: Pcr Assaysmentioning
confidence: 99%
“…The PCRs used were based on those described for detection of the spirochaete species in human colorectal biopsies and faeces [25,28,30]. For B. aalborgi, a 471-bp section of the 16S rRNA gene equivalent to the base-pair positions 172-675 of the 16S rRNA gene of Escherichia coli was targeted for PCR amplification.…”
Section: Pcrsmentioning
confidence: 99%
“…Although one histological study in Southern India demonstrated that IS occurs commonly in apparently healthy villagers [29], the spirochaetes present in these samples were not identified. Recently, the PCR techniques used on DNA extracted from biopsies have been adapted for the detection of B. aalborgi and B. pilosicoli in human faeces [30]. Faecal samples are much easier to obtain than are colorectal biopsies, and hence this technology will facilitate epidemiological studies on these spirochaetes.…”
Section: Introductionmentioning
confidence: 99%